Pengembangan Perangkat Pembelajaran Matematika Berbasis Masalah untuk Melatih Keterampilan Metakognitif Peserta Didik - Bachri, Saiful; Sugianto, Lis; Kriswinarso, Tri Bondan; Lihu, Ikram (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
This research aims to develop the qualified instructional design in Mathematical problem-based learning to increase the Students’metacognitive skills on sine, cosine, and triangles area materials. It used thePlomp model development procedure that consists of the initial investigativephase; the design phase; the realization phase; the testing phase, the evaluation,and revision phase; and the implementation phase. Furthermore, to develop theinstruction, the design was adapted to the characteristic and learning syntaxbased on problem-based learning. The instructional designs that have beendeveloped through this research are lesson plans, material, student worksheets,and achievement tests. Based on the result and try-out that were analyzed, theinstructional design-based problem learning to increase the student’smetacognitive skills of the Tenth Grade of SMA Negeri 3 Palopo on sine, cosine,and triangles materials meets valid, practical, and effective criteria.